An Analysis of Existence of Convergence Between Spot and Futures Prices in Selected Agricultural Commodities - Babshetti, Vaijanath; Basanna, Prakash (Indian Journal of Research in Capital Markets, 2018)
In an efficient derivatives market, as the expiration of futures contract approaches, the spot prices of commodities tend to converge with the futures prices. At any point in time during the expiration period, if the spot prices are higher than the futures prices, it implies that there is a lack of dissemination of proper information at the time of setting the futures prices, and as a result, the futures are undervalued. The current study examined the existence of convergence between spot and futures prices of five selected agricultural commodities namely, chana, cumin, pepper, maize, and chilli during 2011 - 2017. The study also aimed at assessing the scope for arbitrage profit. The negative spread was observed in December 2015 and June 2016 chana futures contracts. In case of cumin, the spot prices were greater than futures at some point of time during the contract period of April 2010 and December 2010, and April and September 2011 contracts. In case of pepper futures, the backwardation was observed in July 2010 and July 2011 expiration, thereby providing scope for arbitrage profit. December 2011 maize contract had a negative basis in the beginning; whereas, December 2013 maize contract had a negative basis throughout the contract period. In case of chilli, the spot prices were higher than the futures prices in April 2012, June 2013, and September 2015 futures contracts. The study revealed the presence of scope for arbitrage profit in these contracts. The study also found the presence of all three types of market patterns in one or the other selected contracts.